LDL CHOLESTEROL ACHIEVEMENT IN HIGH AND VERY HIGH CARDIOVASCULAR RISK PATIENTS ACCORDING TO EUROPEAN SOCIETY OF CARDIOLOGY 2019 GUIDELINE (Vietnam Journal of Community Medicine, 2022)
Objective: To evaluate the rate of target achievement of LDL-C in high and very high cardiovascularrisk patients. Methods: A retrospective study of cardiology outpatient database in Nhan dan GiaDinh Hospital from 2020 January to 2021 January was conducted. Prescriptions before and after lipidinvestigation were collected to consider the statin prescription behavior. Results: LDL-C targetswere achieved in 29.17% and 8.24% of high risk and very high risk patients, respectively. A majority(83.46%) were on intermediate intensity and 16.54% were on high intensity statin treatment. Statindose increment rate was 23.21% in unachieved LDL-C patients. Conclusion: LDL-C achievementrates were modest in high and very high cardiovascular risk patients while the statin prescription wasnot adequate.
Keywords: Dyslipidemia, LDL-C, high and very high cardiovascular risk, statin.